Stress Coping Strategies of Students from Broken Homes - Rizka Puspita Sari; Siti Zahra Bulantika; Rubi Rimonda (Scidacplus, 2025)
The stress experienced by students from broken homes can impact their academic performance and problem-solving abilities. Therefore, this study aims to analyze how stress coping strategies are used by students from broken homes. This study uses qualitative research with a phenomenological design. The research subjects consisted of students at junior high and senior high school levels, and had broken homes. A total of 4 subjects in the research area will be involved as participants, including students from junior high and senior high schools, both public and private schools, to obtain various perspectives and experiences. The data in this study were analyzed using Interpretative Phenomenological Analysis. The results of this study indicate that stress coping strategies used by students in this study include emotion-focused coping and problem focused coping. Both coping strategies are influenced by the presence of social support, personality characteristics, and the type of stressor.